Multi-scale analysis of the synergistic strengthening effect of silane coupling agent on PVA and cement interface - Zhao, Chen; Li, Lijuan; Li, Xiaoyang; Chen, Wuxin; Li, Yongquan (Frontiers in Materials, 2023)
Traditional polyvinyl alcohol (PVA) cementitious composites are susceptible to macroscopic cracking when exposed to impaired compressive strength, reduced toughness, tensile impact and other external loads. In order to solve these problems, a silane coupling agent (KH560) was used to modify PVA fibers, and the influence mechanism of the modification of the admixture was revealed by multi-scale analysis through experimental studies and molecular dynamics simulation. Macroscopic mechanical experiments show that the bending resistance of PVA fiber concrete is significantly improved after the modification of PVA fiber by silane coupling agent. In addition, the incorporation of PVA fibers enhances the toughness of the material and reduces brittle damage. The analysis of microscopic test results showed that SCA modified polymer film played the role of bridging ligaments in the interfacial transition region, effectively preventing crack propagation and enhancing the interfacial adhesion between the organic components of PVA fiber and the cement matrix. Nanoscale molecular dynamics simulation and analysis showed that calcium silicate hydrate exhibited a stable skeleton structure, while the introduction of SCA amplified the hydrogen bond interaction at the interface, thereby enhancing its stability. This study provides valuable insights into the strengthening mechanism of PVA composite concrete and provides a promising avenue for further improvement in this field.